2016
DOI: 10.1002/nag.2534
|View full text |Cite
|
Sign up to set email alerts
|

Population balance in confined comminution using a physically based probabilistic approach for polydisperse granular materials

Abstract: SUMMARYA novel, simplified approach is presented in order to compute variations of grading in granular assemblies during confined comminution under quasi-static compression. The method is based on a population balance equation and requires a breakage probability, considered here as a probabilistic phenomenon that takes into account the particle strength and the loading condition of individual grains. Under basic assumptions, a simple breakage probability can be defined in order to get a valuable result for eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
1
8
1
1
Order By: Relevance
“…measures the difference of the distribution of the contact force between different size fractions. Our simulation results in Figure 10A, as well as the results from Ovalle et al, 13 show that the suggested range of is 0-0.4. The distribution of the contact force of the largest particle size fraction of each gradation is extracted and compared in Figure 10B.…”
Section: Parameter Calibration and Experimental Validationsupporting
confidence: 78%
See 2 more Smart Citations
“…measures the difference of the distribution of the contact force between different size fractions. Our simulation results in Figure 10A, as well as the results from Ovalle et al, 13 show that the suggested range of is 0-0.4. The distribution of the contact force of the largest particle size fraction of each gradation is extracted and compared in Figure 10B.…”
Section: Parameter Calibration and Experimental Validationsupporting
confidence: 78%
“…The parameter controls the shape of the distribution of the normalized contact force. Comparing Equation (11) and Equation (12), is positively related to the particle size and Ovalle et al 13 found the empirical expression ∝ ( ∕ max ) , where = 0.36, through DEM simulations. The DEM simulations also reveal that the value of the maximum size fraction max decreases with the increase of the particle size range.…”
Section: Using the Statistical Entropy To Derive The Contact Force DImentioning
confidence: 97%
See 1 more Smart Citation
“…This is not consistent with what was observed by most researchers that compressed granular assemblies tend toward fractal grading . Mathematical models such as Markov chain model and population balance model were also used recently to estimate grading evolution in granular materials. In addition, Marketos and Bolton developed a probabilistic model to estimate particle crushing in the 1‐dimensional compression of a granular assembly based on data derived from discrete element method (DEM) simulations, making use of the contact force information in the model, as had been increasingly used by others .…”
Section: Introductioncontrasting
confidence: 56%
“…This assumption is reasonable for many granular materials, such as Quartz sands, Quiou limestone sand, Leighton Buzzard silica sand, and Biotite gneiss . For strongly heterogeneous materials, Weibull theory may be invalid after significant breakage …”
Section: Particle Crushing Probabilitymentioning
confidence: 99%